KATA PENYUKAT DALAM BAHASA MINANGKABAU - Ike Revita (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
This study is an attempt to observe the traditional forms and the use of quantity-indicating quantifiers in Minangkabau Language. The data are taken from one of Minangkabau dialects—Tanah Datar. Having been referred to the structural theories, the quantifiers in Minangkabau language are variously categorized based on nouns following as well as the result of the action.